Inhibitors of pan-PI3K Signaling Synergize with BRAF or MEK Inhibitors to Prevent BRAF-Mutant Melanoma Cell Growth - Sweetlove, Melanie; Wrightson, Emma; Kolekar, Sharada; Rewcastle, Gordon W.; Baguley, Bruce C.; Shepherd, Peter R.; Jamieson, Stephen M. F. (Frontiers in Oncology, 2015)
BRAF and MEK inhibitors have improved outcomes for patients with BRAF-mutant melanoma, but their efficacy is limited by both intrinsic and acquired resistance. Activation of the PI3K pathway can mediate resistance to these agents, providing a strong rationale for combination therapy in melanoma. Here, a panel of 9 low passage human metastatic melanoma cell lines with BRAF mutations were tested in cell proliferation and protein expression assays for sensitivity to inhibitors of MEK (selumetinib) and BRAF (vemurafenib) as single agents and in combination with inhibitors of pan-PI3K (ZSTK474), pan-PI3K/mTOR (BEZ235), individual PI3K isoforms (p110α, A66; p110β, TGX-221; p110γ, AS-252424; p110δ, idelalisib), or mTORC1/2 (KU-0063794). Selumetinib and vemurafenib potently inhibited cell proliferation in all cell lines, especially in those that expressed low levels of pAKT. ZSTK474 and BEZ235 also inhibited cell proliferation in all cell lines and enhanced the antitumor activity of selumetinib and vemurafenib in the majority of lines by either interacting synergistically or additively to increase potency or by inducing cytotoxicity by significantly increasing the magnitude of cell growth inhibition. Furthermore, ZSTK474 or BEZ235 combined with selumetinib to produce robust inhibition of pERK, pAKT and pS6 expression and synergistic inhibition of NZM20 tumor growth. The inhibitors of individual PI3K isoforms or mTORC1/2 were less effective at inhibiting cell proliferation either as single agents or in combination with selumetinib or vemurafenib, although KU-0063794 synergistically interacted with vemurafenib and increased the magnitude of cell growth inhibition with selumetinib or vemurafenib in certain cell lines. Overall, these results suggest that the sensitivity of BRAF-mutant melanoma cells to BRAF or MEK inhibitors is at least partly mediated by activation of the PI3K pathway and can be enhanced by combined inhibition of the BRAF/MEK and PI3K/mTOR signaling pathways.